Larval description of Limnephilus atlanticus Nybom 1948, morphological comparison with Limnephilus affinis Curtis 1834, (Trichoptera: Limnephilidae) and additional notes on their ecology in Azores Islands - Balibrea, Ana; Gonçalves, Vitor; Raposeiro, Pedro Miguel (Zootaxa, 2020)
This study presents the first morphological description and illustration of the late instar larva of Limnephilus atlanticus Nybom 1948, an endemic caddisfly from the Azores. Taxonomic comparisons with a recently recorded limnephilid species, Limnephilus affinis (Limnephilidae), and notes of their ecology and distribution in the Azores are also provided.